Impact of Bridge Construction for Improved Livelihood in Rural Area (Nepalese Journal of Development and Rural Studies, 2020)
Nepal has thousands of rivers flowing over its terrain. It needs many bridges for smooth transportation. In this background, this study highlights impact of road bridges like infrastructures on rural livelihood and importance of the local participation in such infrastructure development programme. The study area as the Zone of Influence of ChirdiKhola is ward no. 7 and 10 of Phalebas Municipality which has 1026 households and 4423 populations. Household survey, focus group discussion, key informant interview, observation techniques were used for collecting primary data whereas secondary data were generated from district profile and table review. This study reveals that the bridge has directly or indirectly played crucial role in increasing the freight volume, decreasing the freight cost, increase in number of peoples seeking health facilities through health centers. Local peoples participated to identify the need of bridge and cooperated during the construction of bridge for effective implementation. Motorable Bridge plays vital role in social upliftment and generating the new ideas of income generations. This study also put some light on how Motorable Bridges are constructed in local levels through different programmes, Departments of Nepal Government and the role of District Development Committees in Motorable Bridge projects.